2010
DOI: 10.1159/000265933
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori Tyrosine-Phosphorylated CagA-Related Markers and the Development of Diffuse-Type Gastric Cancers: A Case-Control Study

Abstract: Background/Aims: Tyrosine phosphorylation of the EPIYA motif in Helicobacter pylori CagA (CagA-P) plays an important role in toxic reaction. Diffuse-type gastric cancer (DGC) has a poor prognosis. We tried to clarify the expression level of CagA-P in DGC patients. Methods: We enrolled 42 early-stage DGC patients (DGC group; 20 males, 22 females, mean age 58.2 years) and 42 age- and gender-matched atrophic gastritis (AG) patients (AG group) as controls. We evaluated histological and serological gastritis and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…10 Another of our previous studies also demonstrated that the correlation between the grade of gastritis and gastric carcinogenesis was clearer in women than in men. Generally, malignant tumors as well as IGC are male dominant.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…10 Another of our previous studies also demonstrated that the correlation between the grade of gastritis and gastric carcinogenesis was clearer in women than in men. Generally, malignant tumors as well as IGC are male dominant.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, we have reported the implication of phosphorylated CagA in DGC carcinogenesis and its effect was distinct in women. 10 Another of our previous studies also demonstrated that the correlation between the grade of gastritis and gastric carcinogenesis was clearer in women than in men. 24 The reason is not clear; however, a difference in immunological systems after adhesion of H. pylori may exist.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the latest article, Wada et al examined the expression level of tyrosine phosphorylation of the EPIYA motif in CagA (CagA-P) in diffuse-type gastric cancer patients [51]. The serum titer of anti-CagA-P antibody was significantly higher in the gastric cancer group than in the matched atrophic gastritis group, especially in females.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no reports that examined the prevalence of east Asian type CagA-specific antibodies in sera although there is a sandwich ELISA system to detect east Asian type CagA strains [43]. In addition, Wada et al examined the level of tyrosine phosphorylation of the EPIYA motif in CagA (CagA-P) in patients with diffuse-type gastric cancer in Japan [44]. The serum titer of anti-CagA-P antibodies was significantly higher in the gastric cancer group than in the matched control group.…”
Section: Cytotoxin-associated Gene a Antibodiesmentioning
confidence: 99%